Polish-Ukrainian relations as a factor conditioning the identity of Lviv - Melnyk, Nataliya (Myths and Stereotypes in the Collective Representations, 2019)
The article addresses the problem of shaping the centuries-long relationship between Polish people and Ukrainians from Galicia, and discusses the factors influencing the process of shaping the national identity of the inhabitants of Lvov. The publication underlines the historical and ethnic backgrounds influencing the people living in Lvov region and in Lvov itself. The article also refers to the issue of identifying Lvov residents as Europeans. The author of the article also highlighted obstacles preventing the creation of solid foundation between the inhabitants of Lvov to build a common regional identity despite centuries of co-existence. The destabilizing elements were primarily claims to the same territory. Despite the complicated history, there is one common feature of the Lvov residents which has been preserved – as the author of the article points out – namely, their European identity. This belief has risen to the rank of myth. The article has made a synthetic analysis of the mutual relationship between Polish people and Ukrainians from the 15th century up to the present day, taking into account the influence of elements of collective memory. The current relations between the two nations are relatively well formed. After joining the EU, Poland acts as a Ukrainian supporter, regularly defending its interests. This, as well as the Orange Revolution, Euro 2012 and the Revolution of Dignity contributed to the untightened relations between these two nations. However, despite these positive actions in common relations, the attitude of a decisive part of the intellectual elite of modern Lvov residents is more and more influenced by the mythology of the multiculturalism of this city and its membership “ever since” to Europe, with the dominant Ukrainian language, and simultaneous marginalization of thousand years of belonging to the Polish state, which in effect creates a fake image of the city and its inhabitants.